High-volume resistance training improves double-poling peak oxygen uptake in youth elite cross-country skiers and biathletes: A pilot study - Wagner, C.-M.; Sandbakk, Ø.; Röhrs, D.; Schiemann, S.; Schmidt, T.; Keiner, M. (Applied Sciences, 2025)
A total of nineteen elite youth cross-country skiers (16 ± 2 years) were divided into three groups: a low-load group (LL, n = 6) performing 15-20 repetitions per exercise, a high-load group (HL, n = 9) executing 6-12 repetitions, and a control group (CON, n = 4) exclusively engaging in endurance training. Testing included 1RM in upper-body exercises, VO2max running tests, and double-poling (DP) ergometer exhaustion and sprint tests to determine peak oxygen uptake (VO2peak-DP) and peak power (PP). The results indicated that HL and LL showed significant increases in VO2peak-DP, both in absolute values (d = -1.2 and -1.2, p < 0.05) and when normalized to body mass (d = 0.93 and 1.3, p < 0.05). Although there were no group*time effects for VO2peak-DP, PP during DP tests to exhaustion increased in both HL (d = -1.6, p < 0.05) and LL (d = 1.4, p < 0.05) compared to CON. Standardized to body mass, only HL showed significant improvements in PP during the sprint test (d = 1.7, p < 0.05). During the sprint test, both absolute and body-mass-normalized peak power increased only in the high-load group (d = -1.0 and 0.93, p < 0.05). In conclusion, high-load resistance training resulted in the greatest improvements in strength, DP performance, and VO2peak-DP, indicating a dose-response relationship to the load magnitude of resistance training.